Marketing Communication Strategy Online Product Cell Phone in Attracting Buyers - Astri Dwi Andriani; Muhamad Ramadika (MultiTech Publisher, 2022)
Marketing Communication Strategy for a product in a company is a form of marketing improvement strategy in advancing or improving a company or business actor and making the products offered more popular. The theory used in this research is IMC (Intergrated Marketing Communication). This type of research uses qualitative research with a case study approach. The data sources used were primary and secondary data sources with a total of 5 informants. The data collection techniques used in this research are observation, interviews and documentation.Research results show that Marketing Communication StrategyOnline ProductPainfulAttracting Buyer Interest is said to be good by referring to indicators (1) Advertising (Advertising), where the form of communication is carried out by posting products with photos and descriptions that are clear and easy for buyers to understand, as well as several unique descriptions. Then indicator (2) Sales Promotion (Sales Promotion), namely by providing a packagebundling andflash sale. Indicator (3) Public Relations (Public Relation), where each member maintains communication by posting information, commenting on photos of other members' products and communicating with customers in the comments column, direct messages and evenwhatsapp. Indicator (4) Individual Sales (Personal Selling), namely explaining in language that is easy to understand, providing comments on posts and providing product suggestions if there are customers who are looking for products withrange price or customer requirements. Indicator (5) Direct Sales (Direct Selling), namely communicating with customers who have made several transactions, by offering new or unused products directly throughinbox or numberwhatsapp which has been saved. Then the supporting factors are the seller's consistency in marketing by posting interesting products and information as well as media reachfacebook which is very broad, while the inhibiting factor is that there is still dishonesty, taking a long time to reply to customer messages because they are not read (Slow Respone)